The Effect of Packaging Design on Impulsive Buying Behavior (Case Study on Mentos Products) - Kurnia Sari; Adrian Irnanda Pratama (Inovbiz: Jurnal Inovasi Bisnis Seri Manajemen, Investasi dan Kewirausahaan, 2021)
This study aims to determine the influence of packaging design on implusive buying behavior. This research uses the quantitative approach to explain the connection between two variables, with aims to know: 1) The effect of packaging design on implusive buying behavior. 2) How much the packaging design affect on implusive buying behavior. This research examines the effect of Mentos products at Indomaret Jalan Antara. The data was collected through questionnaires filled out by implusive buyers of Mentos candy. A total of 100 respondents are examined using non-probability sampling. The data analysis used simple regression analysis and hypothesis testing using t test. The result of research showed that: 1) The packaging design has positive significant affect on implusive buying behavior. 2) Packaging design has impluisive buying behavior about 12,5%. Based on the results of research that has been done, reseracher suggest the packaging design is an important thing on marketing aspect.